Future epidemic impact of atrial fibrillation and a new interventional strategy for stroke prophylaxis. (March 2011) - Schmid, Michael; Khattab, Ahmed A; Gloekler, Steffen; Meier, Bernhard
The rising incidence of atrial fibrillation (AF) and its most fatal consequences, cerebral ischemic attacks, will be of increasing relevance in the future. One third to one half of AF patients are ineligible for oral anticoagulation and even after stroke, only approximately every second patient receives oral anticoagulation. Apart from that, the risk of bleeding is indefinite and escalates with age, arterial hypertension, cerebrovascular disease and renal insufficiency. Anticoagulation with new oral compounds may be easier to handle but a significant risk of major bleeding remains. Since over 90% of all thrombi in AF are located in the left atrial appendage (LAA), the idea of excluding this source of emboli, thereby reducing the risk of stroke by approximately 90% without anticoagulation, has arisen. Since 2001, devices for transcatheter occlusion of the LAA have been available, offering a minimally invasive intervention. Currently, two dedicated occluders are approved in Europe, the Amplatzer Cardiac Plug and the WATCHMAN device. Percutaneous occlusion of the LAA is technically feasible and safe and should be considered as an alternative for patients with AF and contraindications or disfavor against oral anticoagulation.